Hedyotis nanlingensis (Rubiaceae), a new species from South China - Wang, Ruijiang; Deng, Shujun; Huang, Xiangxu (Phytotaxa, 2015)
A new species, Hedyotis nanlingensis from Guangdong province, China, is described and illustrated. It is morphologically similar to H. nankunshanensis but differs in the smaller and more slender habit, the sessile leaves, the usually two to three secondary veins on each side of the midvein, the inflorescences with monochasial branching and the shorter style in the long-styled flowers. DNA barcoding analysis demonstrates that all accessions from H. nanlingensis form a monophyletic lineage closely related to H. cantoniensis.